Immunization status and knowledge regarding newer vaccines among mothers in a rural area of Rangareddy District, Telangana, India - M., Vijay Kumar; G., Anjaneyulu; Sree, Venkata Navya; W. M., Gautham Sai (International Journal Of Community Medicine And Public Health, 2016)
Background: India was one of the first countries to adopt the World Health Organization’s Expanded Programme of Immunization (EPI). Many newer vaccines have been added recently in the national immunization schedule some of which are being implemented in a phased manner throughout India. Methods: A community based cross sectional study was done at Yenkapally and Peddamangalaram villages by household survey. Fifty children and their mothers were selected for the study by convenient sampling technique. A pre designed, pre tested questionnaire was used to get the relevant information by adopting interview technique. Questionnaire pertained to socio demographic information, immunization status and knowledge regarding newer vaccines. Results: Out of the 50 children, about three fourths (74%) were completely immunized and 26% were partially immunized. About one third of the mothers were aware about pentavalent vaccination, one fourth were aware about IPV and extreme low level of awareness (2%) was seen regarding rota virus vaccine. Conclusions: Present study found that one fourth of the children were partially immunized with majority missing the booster doses and a very low level of awareness was seen among mothers regarding various newer vaccines.